On the Study of Trigonometric Polynomials Using Strum Sequence - Saiful R. Mondal; Kottakkaran Sooppy Nisar; Thabet Abdeljawad (Journal of Mathematics)
This article constructs trigonometric polynomials of the sine and cosine whose sums are nonnegative. As an application, those nonnegative trigonometric sums are used to study the geometric properties of complex polynomials in the unit disk. The Strum sequences are used to prove the main outcome.